Analysis of validity and reliability of the adapted portuguese version of Antonovsky's Sense of Coherence Questionnaire among nursing professionals (Revista Latino-Americana de Enfermagem, 2011)
This methodological study aimed to evaluate the construct validity and reliability of the Brazilian-Portuguese version of Antonovsky's Sense of Coherence Questionnaire (ASCQ) among nursing professionals. The study included 211 professionals who worked in the surgical wards of eleven hospitals in a city in the interior of the State of Paraná-Brazil. The majority of participants were female (86.7%), with a mean length of service of 9.3 (SD=8.0) years. Construct validity was evaluated using Pearson correlation tests between the measures of sense of coherence and correlated constructs, obtaining strong negative correlations between sense of coherence and anxiety (r=-0.53) and sense of coherence and depression (r=-0.61). Internal reliability, assessed by Cronbach's alpha, obtained an acceptable value of 0.87. The Brazilian-Portuguese version of ASCQ maintained the psychometric properties of the original scale when used with nursing professionals.